Pendidikan Rohani Anak Di Gereja Bethel Tabernakel Ngaliyan Semarang - Eni Rombe; Didasgil SI Taneo; Disetra Fiser Manik (Journal Of Social Empowerment Publications, 2024)
Spiritual education for children at the Beth-El Tabernacle Church in Ngaliyan, Semarang aims to shape Christ-like character in them, encouraging children to know and accept Jesus Christ as their Lord and Savior. Children are taught to understand and practice God's Word in their daily lives, grow in faith, and participate in church services. To support this goal, the PkM team conducted community service activities during the odd semester of 2023/2024 at GBT Ngaliyan, Semarang. This activity, titled "Sunday School Children's Spiritual Education," employed creative and innovative teaching methods, such as Bible stories with props and puppet shows, to create an engaging and enjoyable Sunday school environment. The results of the PkM activities showed high enthusiasm from the children, which helped build their spirituality. The church felt supported and motivated to continue and develop similar activities in the future.